Концептуальні засади забезпечення безпекоорієнтованого розвитку підприємства в Україні - Івченко, А.Г. (Вісник економічної науки України, 2023)
Для формування концептуальних засад забезпечення безпекоорієнтованого розвитку підприємства використано конструктний підхід з урахуванням його переваг та обмежень. До складу концептів увійшли адаптивність як іманентна характеристика підприємства, принциповий вибір діяльності підприємства, пріоритизація безпекоорієнтованого розвитку підприємства, цільова типізація розвитку, цільова векторизація розвитку, шляхи реагування на загрози, ресурсне базування та стратегічний підхід.
Адаптивність визнано необхідно іманентною характеристикою підприємства, а єдино можливим принциповим вибором щодо його діяльності визначено продовження функціонування навіть за складних умов зовнішнього середовища. Для максимально повного якісного опису змісту та якісних характеристик безпекоорієнтованого розвитку підприємства надано його цільову типізацію. Виділено чотири можливі вектори безпекоорієнтованого розвитку підприємства: технологічний, продуктовий, організаційний та ринковий, надано їхню критеріальну характеристику. Для зменшення негативного впливу розглянутих загроз на безпекоорієнтований розвиток підприємства розглянуто шляхи реагування на загрози. Розкрито особливості, переваги та недоліки таких шляхів. Забезпечення безпекоорієнтованого розвитку підприємства у межах концепту ресурсного базування запропоновано здійснювати з використанням його наявних можливостей у забезпеченні безпекоорієнтованого розвитку підприємства. Для цілісного ув’язування та узгодженої операціоналізації наданих концептів необхідний стратегічний підхід, який передбачає доцільність та необхідність формування певного документу забезпечення безпекоорієнтованого розвитку підприємства (стратегії, проєкту, програми, сценарію). To establish the conceptual foundations for ensuring security-oriented development of the enterprise, a constructive approach was employed, considering its advantages and limitations. The concepts include adaptability as an inherent characteristic of the enterprise, the principled choice of the enterprise’s activities, prioritization of security-oriented development, target typification of development, target vectorization of development, responses to threats, resource-based orientation, and a strategic approach. The content of the concepts is disclosed with the aim of their further operationalization, allowing the translation of concept ideas into the practical realm using the appropriate toolkit. Adaptability is recognized as a necessary inherent characteristic of the enterprise, and the only possible principled choice regarding its activities is defined as the continuation of functioning even under challenging external conditions. The challenging operating conditions of domestic enterprises make security-oriented development and its provision a priority in the activities of such enterprises. For a maximally comprehensive qualitative description of the content and qualitative characteristics of security-oriented enterprise development, its target typification is provided: based on the formed set of development criteria, the necessary characteristics are given specifically for security-oriented enterprise development. Vectorization of security-oriented enterprise development characterizes the path to achieving this type of development and gaining market advantages and competitiveness based on it. Four possible vectors of security-oriented enterprise development have been identified: technological, product, organizational, and market, and their criteria characteristics are provided. To mitigate the negative impact of the discussed threats on security-oriented enterprise development, ways to respond to threats have been considered. The features, advantages, and disadvantages of such approaches are disclosed. Ensuring security-oriented enterprise development within the concept of resource-based orientation is proposed to be carried out using its available capabilities to ensure security-oriented enterprise development. For each development vector, the opportunities that most contribute to a specific vector of development are highlighted, allowing the selection of a relevant vector for the enterprise based on available opportunities in each specific case. For the comprehensive integration and coordinated operationalization of the provided concepts, a strategic approach is necessary, which entails the feasibility and necessity of forming a specific document to ensure security-oriented enterprise development (strategy, project, program, scenario).